2010
DOI: 10.1038/ejcn.2010.139
|View full text |Cite
|
Sign up to set email alerts
|

Intake of n-3 polyunsaturated fatty acids and non-alcoholic fatty liver disease: a cross-sectional study in Japanese men and women

Abstract: Background/Objectives: Non-alcoholic fatty liver disease (NAFLD) is a common condition, in which abnormal amounts of triglycerides accumulate in hepatocytes and is closely related to cardiovascular diseases and diabetes. Dietary fats contribute 15% of fat accumulation in the liver and regulate hepatic lipid metabolism. The supplementation of n-3 polyunsaturated fatty acids (n-3 PUFAs) improves NAFLD. The aim of this study is to assess the cross-sectional association between dietary n-3 PUFAs and NAFLD in Japan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 37 publications
2
25
0
1
Order By: Relevance
“…It was consistent with a previous study that DHA alleviates lipid deposition and inflammation and the supplementation of n-3 PUFAs ameliorates NAFLD in Japanese men and women [32]. However, the exact mechanisms of DHA in preventing NASH are not yet clear.…”
Section: Discussionsupporting
confidence: 92%
“…It was consistent with a previous study that DHA alleviates lipid deposition and inflammation and the supplementation of n-3 PUFAs ameliorates NAFLD in Japanese men and women [32]. However, the exact mechanisms of DHA in preventing NASH are not yet clear.…”
Section: Discussionsupporting
confidence: 92%
“…Precise dietary intake was not examined in this study, but younger patients with NAFLD tended to consume high fat and high carbohydrate diets, and meat more than fish. This tendency was in accordance with previous reports . It was reported that the EPA/AA ratio of healthy Japanese living in urban areas was elevated stepwise with age: less than 35 years, 0.26 ± 0.17; 35–44 years, 0.29 ± 0.13; 45–54 years, 0.43 ± 0.23; 55–64 years, 0.58 ± 0.25; and 65 years or more, 0.68 ± 0.22 .…”
Section: Discussionsupporting
confidence: 93%
“…89 Patients with NAFLD, and especially those with histologically confirmed NASH, have been found to not only consume less o-3 FA but also have less hepatocellular o-3 FA. 90,91 Intervention studies show variable results. Supplementation with EPA for 1 year led to decreased hepatic steatosis (diagnosed through imaging) and transaminase levels in 14 patients with NAFLD, 92 whereas 9 g/d of fish oil given to a different cohort of 22 obese adults for 4 weeks did not lead to significant changes in the degree of steatosis compared with placebo.…”
Section: Pufamentioning
confidence: 97%